Resin composition and sheet molding compound, and alumina particles used in resin composition

By using compositions of high water content alumina particles and resins in semiconductor packaging materials, the problem of high charge amount of packaging materials resulting in fine dust adsorption is solved, and a lower charge amount and higher performance of packaging materials are achieved.

JP2025060438APending Publication Date: 2025-04-10SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024155268
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-09
Publication Date
2025-04-10

Smart Images

  • Figure 2025060438000001
    Figure 2025060438000001
  • Figure 2025060438000002
    Figure 2025060438000002
  • Figure 2025060438000003
    Figure 2025060438000003
Patent Text Reader

Abstract

To provide a resin composition containing alumina particles and a resin, the resin composition having a reduced quantity of electric charge as compared with the conventional art.SOLUTION: Provided is a resin composition containing alumina particles and a resin, wherein the alumina particles generate moisture in an amount exceeding 59.8 ppm when heated from 200°C to 900°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to resin compositions and sheet molding compounds, as well as alumina particles for use in the resin compositions. [Background technology]

[0002] Heat generated by passing electricity through electronic components is likely to adversely affect the performance of the electronic components, so it is desirable to dissipate the heat quickly. Therefore, for example, it is desirable for the material constituting the semiconductor sealing member surrounding the IC chip to exhibit high thermal conductivity for heat dissipation. The sealing member may generally contain inorganic particles (e.g., alumina particles) and resin, as described in Patent Document 1. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-200478 A Summary of the Invention [Problem to be solved by the invention]

[0004] If dust or the like adheres during the manufacture of a semiconductor device, it can cause defective products. In particular, in recent years, with the miniaturization of semiconductor devices and the narrowing of wiring pitches, even the adhesion of fine dust has become a problem. In order to more reliably suppress the adhesion of fine dust, it is required that the amount of charge of the resin composition used in the semiconductor sealing member is reduced more than ever before. However, a specific method for reducing the amount of charge of the resin composition more than ever before is not known. Patent Document 1 makes no consideration at all about the charge amount of the resin composition.

[0005] In view of the above circumstances, an object of one embodiment of the present invention is to provide a resin composition containing alumina particles and a resin, which has a lower amount of electrostatic charge than conventional resin compositions. Another embodiment of the present invention has an object to provide a sheet-shaped composition (sheet molding compound) comprising such a resin composition. Yet another embodiment of the present invention is directed to providing alumina particles for use in a resin composition. [Means for solving the problem]

[0006] Aspect 1 of the present invention is Alumina particles having a moisture content of more than 59.8 ppm when heated from 200°C to 900°C; Resin and The resin composition includes:

[0007] Aspect 2 of the present invention is The alumina particles are the resin composition according to aspect 1, in which an amount of moisture generated upon heating from 200° C. to 550° C. is more than 43.0 ppm.

[0008] Aspect 3 of the present invention is In the resin composition according to aspect 1 or 2, the alumina particles have an absolute charge of 0.17 kV or less.

[0009] A fourth aspect of the present invention is Alpha radiation dose is 0.022cph / cm 2 The resin composition according to any one of Aspects 1 to 3, wherein the viscosity is less than 100 μm.

[0010] A fifth aspect of the present invention is In the resin composition according to any one of Aspects 1 to 4, the alumina particles have a ratio (L2 / L1) of the total length L2 of the internal grain boundaries to the length L1 of the outer edge of the alumina particles is less than 139.1%.

[0011] A sixth aspect of the present invention is The resin composition according to any one of aspects 1 to 5 is used. A sheet molding compound having a thickness of 1000 μm or less.

[0012] A seventh aspect of the present invention is These are alumina particles that generate more than 59.8 ppm of moisture when heated from 200°C to 900°C. Effect of the Invention

[0013] According to one embodiment of the present invention, it is possible to provide a resin composition having a lower charge amount than conventional resin compositions. According to another embodiment of the present invention, there is provided a sheet molding compound comprising such a resin composition. According to yet another embodiment of the present invention, alumina particles for use in a resin composition can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In order to reduce the risk of fine dust adhering to the resin composition as much as possible, the inventors have conducted extensive research into a resin composition having a lower charge amount than in the past. As a result, they have found for the first time that the charge amount of the resin composition can be effectively reduced by setting the moisture content of the alumina particles used in the resin composition to a certain amount or more, and have completed the present invention.

[0015] The resin composition according to the embodiment, the alumina particles used in the resin composition, and the sheet molding compound (SMC) made of the resin composition will be described below.

[0016] [Resin composition] The resin composition according to the present embodiment contains alumina particles and a resin. The alumina particles used have a moisture content of more than 59.8 ppm when heated at 200° C. to 900° C. In this specification, the term "resin composition" is intended to include all of the resin compositions in the liquid state before the resin in the resin composition is cured, the semi-cured state (B stage) in which the resin is semi-cured, and the cured state (C stage) in which the resin is completely cured. Here, the "liquid state" includes compositions in which the resin composition has fluidity, such as resin compositions containing a solvent described below. "Semi-cured" refers to a state in which the resin composition is cured to an extent that it can be handled as a solid, but is not completely cured, and therefore the surface of the resin composition is sticky. "Cured state" refers to a state in which the resin composition can be handled as a solid and has almost no stickiness on the surface.

[0017] Regarding the charge amount of the resin composition, the lower the absolute value of the charge amount, the less likely the resin composition is to be charged and the less likely dust will adhere to it. The inventors have found that the absolute value of the charge amount of the resulting resin composition can be reduced by forming a resin composition using alumina particles whose moisture content is controlled to be a certain amount or more. In the resin composition according to the embodiment, the absolute value of the charge amount of the resin composition can be set to 0.00 kV (substantially uncharged) by using alumina particles whose moisture content generated by heating from 200°C to 900°C is more than 59.8 ppm. Therefore, the resin composition according to the embodiment can effectively suppress the adhesion of fine dust.

[0018] The alpha dose of the resin composition is 0.022 cph / cm 2 It is preferable that the α-ray dose is less than 0.020 cph / cm. This is because semiconductor devices are easily affected by α-rays, and malfunctions (soft errors) caused by α-rays are likely to become a problem. In addition, it is expected that a low α-ray dose will make it difficult for the resin composition to be charged by the ionizing effect of α-rays. Therefore, it is considered that a resin composition with an extremely low charge amount can be formed relatively easily. The α-ray dose of the resin composition is preferably 0.020 cph / cm. 2 or less, more preferably 0.015 cph / cm 2 Less than 0.005 cph / cm, more preferably 0.005 cph / cm 2 Less than 0.002 cph / cm is particularly preferable.2 In particular, the alpha radiation dose of the cured resin composition is 0.022 cph / cm 2 Less than 0.020cph / cm 2 Below, 0.015cph / cm 2 Below, 0.005cph / cm 2 Less than or equal to 0.002cph / cm 2 The lower the alpha dose of the resin composition, the more preferable. The lower limit is preferably 0.000 cph / cm 2 The alpha radiation amount of the resin composition is measured in a semi-cured or cured state using an alpha radiation measuring device (e.g., Model 1950 manufactured by Alpha Sciences, Inc.). The measurement area of ​​the sample is 1000 cm. 2 The measurement time is 99 hours, and the counting gas used is PR-10 gas (Ar 90%, CH4 10%).

[0019] The breaking stress measured in the semi-cured or cured resin composition is preferably more than 41.2 MPa, more preferably 50.0 MPa or more, even more preferably 60.0 MPa or more, and particularly preferably 65.0 MPa or more. In particular, the breaking stress of the cured resin composition is preferably more than 41.2 MPa, 50.0 MPa or more, 60.0 MPa or more, or 65.0 MPa or more in this order. This improves the strength when used as a sealing member, and can also improve the dimensional stability against external energy such as heat. The breaking stress of the resin composition can be calculated from a stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The breaking stress of the semi-cured and cured resin compositions can be increased by adjusting the content of alumina particles and the curing conditions. Usually, the breaking stress is higher in the cured resin composition than in the semi-cured state.

[0020] The absorption energy until breakage measured in the semi-cured or cured resin composition is preferably 0.200 MPa or more, more preferably more than 0.314 MPa, even more preferably more than 0.400 MPa, even more preferably more than 0.500 MPa, and particularly preferably more than 0.600 MPa. In particular, the absorption energy until breakage of the cured resin composition is preferably more than 0.314 MPa, 0.400 MPa or more, 0.500 MPa or more, or 0.600 MPa or more in this order. This improves the strength when used as a sealing member, and can also improve the dimensional stability against external energy such as heat. The absorption energy until breakage of the resin composition can be calculated from the area surrounded by the stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The absorption energy until breakage of the semi-cured and cured resin compositions can be increased by adjusting the content of alumina particles and the curing conditions. Usually, the absorption energy until breakage is higher in the cured resin composition than in the semi-cured state.

[0021] The correlation coefficient when the stress-strain curve measured in the semi-cured or cured resin composition until breakage is linearly approximated is preferably greater than 0.9765. A large correlation coefficient indicates that the resin composition stretches uniformly, and may mean that, for example, inorganic particles are not aggregated with each other and are uniformly dispersed in the resin. In this case, moderate interaction between the particles and the resin is easily achieved, and dimensional stability against external energy such as heat is easily ensured. The correlation coefficient is preferably 0.9780 or more, more preferably 0.9795 or more. In particular, the correlation coefficient when the stress-strain curve of the cured resin composition until breakage is linearly approximated is preferably greater than 0.9765, 0.9780 or more, or 0.9795 or more, in that order. The upper limit of the correlation coefficient is 1.0000.

[0022] Since the alumina particles can form a resin composition without impairing the flexibility peculiar to the resin, the blending ratio is preferably in the order of 5-75% by volume of resin, 95-25% by volume of alumina particles, or 8-50% by volume of resin, 92-50% by volume of alumina particles, or 10-40% by volume of resin, 90-60% by volume of alumina particles, or 12-40% by volume of resin, and 88-60% by volume of alumina particles, in the total ratio to the total resin composition, in the semi-cured and cured resin compositions, the total ratio of the resin and the alumina particles to the total resin composition is preferably 60% by volume or more, more preferably 70% by volume or more, and even more preferably 80% by volume or more. Furthermore, in the semi-cured and cured resin compositions, the ratio of the solid content to the total resin composition is preferably 80% by volume or more, more preferably 90% by volume or more, and even more preferably 95% by volume or more. The solid content of a resin composition refers to what remains as a solid when the resin composition is heated, excluding, for example, the solvent and other components that volatilize upon heating. On the other hand, even if a component is liquid at 25°C, if it is incorporated into the solid content of the resin composition when heated, it is included in the solid content. The proportion of the solid content can be determined, for example, by determining the amount of solvent in the resin composition and subtracting it from the total. The amount of solvent in the resin composition can be measured, for example, by the following method. After measuring the mass W1 (g) of the resin composition, the sample is heated at 150°C for 10 minutes using a total exhaust oven to evaporate all the solvent contained in the sample, and then the sample is left at room temperature for 5 minutes to return to room temperature, and the mass W2 (g) of the sample after heating is measured. The amount of solvent in the resin composition can be determined by subtracting W2 (g) from W1 (g).

[0023] Next, the alumina particles and the resin that constitute the resin composition will be described in detail.

[0024] [Alumina particles] The alumina particles according to this embodiment have the following characteristics. The alumina particles preferably contain α-alumina particles. The α-alumina is expected to have an effect of reducing the amount of α-rays emitted from the alumina particles, and the presence of the α-alumina particles in the alumina particles can improve the effect of suppressing the amount of α-rays emitted from the resin composition. The α-alumina particles are also expected to have an effect of reducing the dielectric loss of the resin composition.

[0025] (Moisture content of alumina particles) The alumina particles according to the embodiment have a moisture content (sometimes referred to as a "total moisture content") of more than 59.8 ppm that is generated when heated from 200° C. to 900° C. By using alumina particles containing a certain amount or more of moisture, the charge amount of the resin composition can be effectively reduced. The total moisture content of the alumina particles is preferably 70.0 ppm or more, more preferably 80.0 ppm or more, and particularly preferably 95.0 ppm or more. The upper limit of the total moisture content of the alumina particles is not particularly limited from the viewpoint of reducing the charge amount of the resin composition, but may be 200.0 ppm or less.

[0026] Of the total moisture content of the alumina particles, the amount of moisture generated upon heating from 200°C to 550°C (sometimes referred to as the "low-temperature side moisture content") may have a significant effect on the charge amount of the resin composition. The low temperature side moisture content is preferably controlled to more than 43.0 ppm, which makes it possible to further reduce the amount of electrostatic charge in the resin composition. The low-temperature side moisture content of the alumina particles is more preferably 60.0 ppm or more, further preferably 70.0 ppm or more, and particularly preferably 80.0 ppm or more. The upper limit of the low-temperature side moisture content of the alumina particles is not particularly limited from the viewpoint of reducing the charge amount of the resin composition, but may be 185.0 ppm or less.

[0027] The moisture content of the alumina particles (total moisture content and low temperature moisture content) is measured based on the Karl Fischer titration method (moisture vaporization-titration method) in accordance with JIS K 0068:2001 "Method of measuring moisture content in chemical products."

[0028] (Amount of charge on alumina particles) The alumina particles according to the embodiment preferably have an absolute value of the charge of 0.17 kV or less. This can reduce the charge of the resin composition and improve the dispersibility of the alumina particles in the resin. In other words, the alumina particles are relatively uniformly dispersed in the resin composition, and the physical properties of the resin composition (breaking stress, absorbed energy until breakage, correlation coefficient when the stress-strain curve of the resin composition until breakage is linearly approximated) can be improved. The charge amount of the alumina particles can be affected by the amount of moisture contained in the alumina particles, the unevenness of the alumina particle surface, the disorder of the crystal structure of the alumina particles, etc., but it is considered that the effect of the moisture amount is particularly large. Therefore, the charge amount can be controlled by controlling the moisture amount of the alumina particles.

[0029] The absolute value of the charge of the alumina particles is more preferably 0.15 kV or less, even more preferably 0.10 kV or less, particularly preferably 0.08 kV or less, particularly more preferably 0.05 kV or less, and most preferably 0.02 kV or less. The lower the absolute value of the charge of the alumina particles, the better, and the preferred lower limit is 0.00 kV. The charge amount of the alumina particles is measured by a static electricity measuring device in accordance with JIS C 61340-2-1. For example, it can be measured by using a commercially available potential measuring device, a coulomb meter, a Faraday cage, or the like.

[0030] When measuring the moisture content and charge amount of the alumina particles in the resin composition, first, the resin contained in the resin composition is removed, for example, by dissolving it in an organic solvent, and only the alumina particles are separated. The moisture content and charge amount can be measured using the separated alumina particles.

[0031] (Uranium and Thorium Content) The alumina particles have a uranium content of less than 550 ppb and a thorium content of less than 10 ppb. The uranium and thorium contents of the alumina particles are suppressed to very small amounts as described above, so that the amount of α-rays emitted from the alumina particles can be reduced, and as a result, the amount of α-rays emitted from the resin composition can be suppressed. This makes it possible to suppress malfunction of the semiconductor device due to α-rays when used as an encapsulating material for the semiconductor device.

[0032] The uranium content is preferably 300 ppb or less, more preferably 100 ppb or less, even more preferably 50 ppb or less, particularly preferably 30 ppb or less, for example 10 ppb or less, or 5 ppb or less. The lower limit of the uranium content is not particularly limited, but may be 0.1 ppb or more. The thorium content is preferably 8 ppb or less, more preferably 5 ppb or less, and particularly preferably 2 ppb or less. The lower limit of the thorium content is not particularly limited, but may be 0.1 ppb or more. The uranium and thorium contents can be measured using inductively coupled plasma mass spectrometry (ICP-MS).

[0033] (The ratio of the total length L2 of the grain boundaries inside the alumina particle to the outer edge length L1 of the particle) By reducing the grain boundary content in the alumina particles, the shielding effect against alpha rays generated from uranium and thorium in the alumina particles can be improved, and the amount of alpha rays emitted from the alumina particles can be reduced. In this embodiment, the ratio of the total length L2 of the grain boundaries to the length L1 of the outer edge (L2 / L1) is introduced as an index of the content of grain boundaries inside an alumina particle. L1 and L2 are determined by observing a cross section of the alumina particle.

[0034] When the length of the outer edge of one alumina particle is L1 and the total length of the grain boundaries of the alumina particle is L2, it can be said that alumina particles with a small value of L2 / L1 have a small content of grain boundaries and emit a low amount of α-rays. In particular, it is preferable that (L2 / L1) (%) is less than 139.1%, which can further reduce the amount of α-rays emitted when used as a filler for a resin composition. By reducing the amount of α-rays emitted from the alumina particles, the amount of α-rays emitted from a resin composition containing the alumina particles can also be reduced.

[0035] (L2 / L1) is preferably 120.0% or less, more preferably 100.0% or less, even more preferably 80.0% or less, even more preferably 60.0% or less, particularly preferably 52.0% or less, and most preferably 50.0% or less. The lower limit of (L2 / L1) is not particularly limited, but may be 10.0% or more, for example, 20.0% or more, 30.0% or more, 40.0% or more, or 43.0% or more. When the lower limit of L2 / L1 is within the above range, the interaction between the particles and the resin becomes easier to work, and in particular, the mechanical strength such as the breaking stress of the resin composition after semi-curing and curing is easily increased. In order to control this L2 / L1 within a suitable range, single crystal raw material particles may be used.

[0036] The "total length L2 of grain boundaries" refers to the sum of the grain boundaries contained inside an alumina particle, and does not include the outer edge of the alumina particle. The total length L2 of grain boundaries is the sum of the total length L3 of grain boundaries inside an alumina particle and the total length L4 of the inner wall of the cavity (if there is a cavity inside the alumina particle) (i.e., L2 = L3 + L4).

[0037] (Particle size of alumina particles) The alumina particles preferably have a particle diameter D50 of 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less, even more preferably 10 μm or less, particularly preferably 5 μm or less, and most preferably 3 μm or less, in which case the particle diameter D50 is within the above range, making it possible to form a resin composition suitable for miniaturizing semiconductor devices and narrowing the wiring pitch.

[0038] The alumina particles preferably have a ratio D90 / D50 of 5.0 or less, where D90 is the cumulative 90% particle size from the fine particle side of the cumulative particle size distribution (hereinafter sometimes simply referred to as "D90") and D50 is the cumulative 50% particle size from the fine particle side of the cumulative particle size distribution (hereinafter sometimes simply referred to as "D50"). This makes the particle size distribution sharp, and makes it easier for a suitable interaction to occur between the particles and the resin, and in particular makes it easier to increase the mechanical strength, such as the breaking stress, of the resin composition after semi-curing and curing. For example, D90 / D50 is more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 1.5 or less.

[0039] On the other hand, if the particle size distribution of the alumina particles is broad to some extent, the filling property is improved by allowing small particles to enter the gaps between the large particles, and more alumina particles can be kneaded into the resin, which can improve the dimensional stability and breaking stress against external energy such as heat. Therefore, D90 / D50 is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more.

[0040] The particle diameters D50 and D90 of the alumina particles can be determined by measuring the particle size distribution of the alumina particles by laser diffraction using, for example, a Microtrack MT3300EXII laser particle size distribution measuring device manufactured by Microtrack Bell Co., Ltd., and determining D50 and D90. The particle size of the alumina particles in the resin composition can be measured by removing the resin contained in the resin composition, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to pyrolyze the resin, isolating only the alumina particles, and using the alumina particles.

[0041] Another method for determining D50 and D90 of alumina particles is a method using image analysis. The resin composition may be subjected to cross-sectional observation with an SEM, and all alumina particles contained in a predetermined observation area (e.g., 200 μm×200 μm) may be subjected to image analysis, and the particle diameters equivalent to D50 and D90 may be calculated based on the measurement results of their particle diameters (equivalent circle diameters).

[0042] [Method of manufacturing alumina particles] The alumina particles according to this embodiment can be produced, for example, by the method described below.

[0043] (Raw alumina) The raw alumina is produced by a known method, such as the Bayer method, the ammonium alum method, the ammonium aluminum carbonate hydroxide method (AACH method), the solvent extraction method, the organoaluminum hydrolysis method (aluminum alkoxide method), the CZ method, the Verneuil method, the chiroporous method, the Bridgman method, the EFG method, or other melt growth methods.

[0044] In the case of the Bayer process, raw alumina can be produced by calcining aluminum hydroxide obtained from bauxite. In addition, the ammonium alum process, the AACH process, the solvent extraction process, and the aluminum alkoxide process are preferable because they can produce high-purity raw alumina with low uranium and thorium contents. If raw alumina produced by these methods, with a uranium content of less than 550 ppb and a thorium content of less than 10 ppb, is used to produce alumina particles, it is preferable because alumina particles with low uranium and thorium contents can be obtained.

[0045] (Crushing raw alumina) In order to easily obtain alumina particles of a desired size by flame melting, the raw alumina is pulverized to obtain an alumina raw powder to be subjected to flame melting. The raw alumina can be pulverized by a known method such as a vibration mill, a bead mill, a ball mill, or a jet mill, and may be pulverized in either a dry or wet state.

[0046] In the above-mentioned pulverization, a surface protective agent may be used. The surface protective agent may not only protect the surface of the alumina raw material powder after pulverization, but also have the function of inactivating the surface of the alumina raw material powder. The surface protective agent can reduce the aggregation of the alumina raw material powders themselves due to its function of inactivating the surface, and is therefore suitable for obtaining alumina particles of a desired particle size after flame fusion using raw material alumina with a high BET specific surface area that is prone to aggregation. Suitable surface protective agents include, for example, monohydric alcohols such as methanol, ethanol, 1-propanol, and 2-propanol; glycols such as ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol; amines such as triethanolamine; and higher fatty acids such as palmitic acid, stearic acid, and oleic acid. Of these surface protective agents, one type may be used alone, or two or more types may be used in combination. Of these, glycols are preferred, and in particular, one or more types of ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol are preferred.

[0047] For example, polyethylene glycol and polypropylene glycol, which are preferably used as surface protective agents, are not particularly limited in terms of their molecular weight, but liquid ones with an average molecular weight of about 200 to 600 are preferred for ease of addition.

[0048] The amount of the surface protective agent added is preferably 0.01 parts by mass or more in order to fully exert the effect of the surface protective agent when the raw material alumina is taken as 100 parts by mass, and is preferably 10 parts by mass or less because the effect of the surface protective agent becomes saturated if the amount of the surface protective agent added is too large. The amount of the surface protective agent added is more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass.

[0049] (Flaming) The flame fusion method is a method in which raw alumina is sprayed into a flame, turned into droplets, and then cooled and solidified. According to the flame fusion method, alumina particles can be obtained while maintaining the particle size of the raw alumina. In the flame fusion method, the temperature of the flame fusion furnace is preferably 1000°C or higher. In the flame fusion method, the raw material supply rate can be appropriately adjusted, but by setting it to preferably 50 kg / h or less, more preferably 10 kg / h or less, the amount of thermal energy applied to the alumina particles can be controlled within a specified range, making it easier to obtain alumina particles that meet the above-mentioned specified requirements.

[0050] After the flame melting, the alumina particles are collected using a cyclone or a bag filter and classified to obtain alumina particles having desired properties.

[0051] The moisture content of the alumina particles can be controlled by the conditions of the manufacturing method of the raw alumina, the pulverization method, and the flame fusion method, but it can also be controlled by immersing the obtained alumina particles in an acidic solution such as hydrochloric acid. The type of acidic solution used during immersion is preferably hydrochloric acid because of the ease of concentration adjustment. The concentration of the acidic solution is preferably adjusted to 1M to 12M, more preferably 1M to 10M, and particularly preferably 2M to 5M. The mass ratio during immersion is preferably alumina particles:acidic solution of 1:2 to 1:10. The immersion time is preferably 5 hours or more. During immersion, heating may be performed appropriately to shorten the immersion time, for example, heating may be performed to 50 to 90°C. After immersion, washing and drying are preferably performed.

[0052] [resin] The resin used in the resin composition preferably contains one or more selected from the group consisting of epoxy resins and thermoplastic polyimides, and more preferably contains an epoxy resin. Preferred epoxy resins include mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins. The mesogenic epoxy resin is an epoxy resin having a mesogenic group, and is preferably a resin that exhibits a phase transition temperature in the temperature range of 100°C to 200°C to be sealed and exhibits liquid crystallinity. The resin contained in the resin composition may contain one or more epoxy resins. That is, the resin contained in the resin composition may contain one or more epoxy resins selected from the group consisting of mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins, and may further contain a thermoplastic polyimide. These resins are expected to have an effect of blocking alpha rays emitted from the alumina particles, so that a resin composition with even lower alpha radiation levels can be obtained.

[0053] Furthermore, these resin compositions may be appropriately mixed with known additives such as plasticizers, curing agents, curing accelerators, coupling agents, fillers, pigments, flame retardants, antioxidants, surfactants, compatibilizers, weather resistance agents, antiblocking agents, antistatic agents, leveling agents, and release agents, either singly or in combination, as long as the effects of the invention are not impaired. In addition, as an embodiment of the present application, the resin composition (particularly, a resin composition in a liquid state or a semi-cured state) may contain a solvent, and when the resin composition contains a solvent, it is easy to flow, can be easily deformed to match the fine structures of IC chips and substrates, and can seal dense structures without gaps. As the solvent, known solvents can be used, and are not limited as long as the resin can be dissolved therein, and examples thereof include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, amine-based solvents, amide-based solvents, halogen-based solvents, hydrocarbon-based solvents, and nitrile-based solvents. Ketone-based solvents and ester-based solvents are preferred from the viewpoint of being good solvents for epoxy resins and excellent coating properties of the resulting resin composition.

[0054] In a preferred embodiment of the present invention, the resin composition comprises alumina particles, an epoxy resin, a solvent, and a hardener, such as an amine-based hardener such as 4,4-diaminodiphenylmethane.

[0055] [Method of producing resin composition] A method for producing the resin composition will be described. A resin composition can be obtained by mixing the alumina particles according to the present embodiment with a resin using a commonly used known method. For example, when the resin is liquid (e.g., liquid epoxy resin, etc.), the resin composition can be obtained by mixing the liquid resin, alumina particles, and a curing agent, and then curing with heat or ultraviolet light. Known curing agents and known methods can be used as the curing agent, mixing method, and curing method. On the other hand, when the resin is solid (e.g., epoxy resin, polyolefin resin, acrylic resin, etc.), the alumina particles and the resin are mixed, and then kneaded by a known method such as melt kneading, or the resin, alumina particles, and a curing agent are dissolved and mixed in a solvent to obtain the desired resin composition. The resin composition may contain a solvent.

[0056] The resin composition according to this embodiment includes a resin composition in all states, including a liquid state before the resin in the resin composition is cured, a semi-cured state (B stage) in which the resin is semi-cured, and a cured state (C stage) in which the resin is completely cured. The resin composition in a liquid state includes a compound in which alumina powder and a resin are mixed in a predetermined mixing ratio, a mixture obtained by mixing the compound, and a molded product obtained by molding the mixture. The semi-cured resin composition includes a resin composition obtained by semi-curing a resin contained in a mixture or a molded product. The cured resin composition includes a resin composition obtained by completely curing a resin contained in a mixture, a molded product, or a semi-cured product.

[0057] [Sheet Molding Compound (SMC)] The resin composition according to the embodiment can be used to provide a sheet molding compound (SMC). The SMC is a resin composition molded into a sheet. The SMC is preferably one that has flowability when heated and pressurized, and may be in a semi-cured state. The thickness of the SMC is preferably 1000 μm or less, and when incorporated into a semiconductor device, the semiconductor device can be made smaller and lighter, and when sealing an IC chip, the sealing performance can be improved. The thickness is more preferably 800 μm or less, even more preferably 600 μm, even more preferably 500 μm or less, particularly preferably 400 μm or less, and particularly preferably 300 μm or less. The lower limit of the thickness is not particularly limited, but from the viewpoint of the dimensions of SMCs generally used and improving the sealing performance of IC chips, it may be, for example, 10 μm or more, 50 μm or more, or even 100 μm or more, or 150 μm or more.

[0058] The SMC can be prepared by a known method. As an example, an uncured resin composition is applied onto a substrate, a protective film is placed thereon, and the resin composition is semi-cured. As another example, an uncured resin composition containing a solvent is applied onto a substrate, the solvent is removed from the resin composition by drying or the like, and then a protective film is placed. When using the SMC, the protective film is peeled off, the SMC is pressed against a wafer or the like, the substrate is removed, and the SMC is post-cured.

[0059] The resin composition and SMC of the present invention have a low alpha radiation dose and are therefore suitable as sealing materials for semiconductor elements. EXAMPLES

[0060] [Creation of alumina particles] The alumina particles (A to C) used in the resin compositions of Samples No. 1 to 5 were prepared as follows.

[0061] (Alumina particles A and B used in samples No. 1 to 4) As the alumina particles, the following alumina particles A (used for samples Nos. 3 and 4) and alumina particles B (used for samples Nos. 1 and 2) were prepared.

[0062] The raw alumina used was γ-alumina obtained by the ammonium alum method (the average particle size of the primary particles calculated from the BET specific surface area value below was 13 nm). The BET specific surface area of ​​this γ-alumina measured by the nitrogen adsorption method was 120 m 2 Before pulverization, 4% by mass of propylene glycol was added as a surface protective agent to the raw alumina and mixed.

[0063] Next, the alumina was processed using a jet mill pulverizer (horizontal jet mill pulverizer PJM-280SP manufactured by Japan Pneumatic Mfg. Co., Ltd.) under the conditions of a feed rate of the raw alumina of 30 kg / h and a gauge pressure of the air supply port during pulverization of 0.5 MPa, to obtain an alumina raw powder with an average secondary particle size of approximately 2 μm.

[0064] The obtained alumina raw material powder was put into a flame melting furnace and melted to obtain spherical alumina particles. The atmospheric temperature in the flame melting furnace was set to 1250°C, and the raw material supply rate was set to 5 kg / h. The obtained alumina particles were collected by a cyclone and classified by cyclone classification to remove particles of 20 μm or more to obtain alumina particles A (D50=5.1 μm, used for samples No. 3-4). Furthermore, particles of 10 μm or more were removed to obtain alumina particles B (D50=2.3 μm, used for samples No. 1-2).

[0065] (Alumina particle C used in sample No. 5) For sample No. 5, alumina particles (alumina particles C) of DAW05 manufactured by Denka were used.

[0066] The alumina particles used in each sample were subjected to the following measurements.

[0067] [Particle size distribution of alumina particles] The D50 and D90 of the alumina particles were measured by the laser diffraction method using a Microtrack MT3300EXII laser particle size distribution measuring device manufactured by Microtrack Bell Co., Ltd. The D50 and D90 were obtained from the particle size distribution measurement results. The alumina particles to be measured were added to a 0.2 mass% sodium hexametaphosphate solution so that the laser scattering intensity was appropriate, and the alumina particle dispersion was dispersed for 5 minutes using the built-in ultrasonic of 40W. The refractive index of alumina was set to 1.76.

[0068] [Amount of charge on alumina particles] The charge amount of the alumina particles was measured using a static electricity measuring device under the following conditions. Static electricity measuring instrument: FMX-004 (manufactured by SIMCO) Measurement mode: Low Mode ·Temperature 23℃, humidity 40% 10 g of alumina particles were placed in an aluminum cup, and a static electricity measuring device was placed 25 mm above the surface to measure the charge potential. The obtained charge potential value is defined as the charge amount.

[0069] [Moisture content of alumina particles] The moisture content of the alumina particles was measured based on the Karl Fischer titration method (moisture vaporization-titration method) in accordance with JIS K 0068:2001 "Method for measuring moisture content in chemical products." Two moisture content measurements were made: the amount of moisture generated by heating from 200°C to 550°C (low-temperature moisture content), and the amount of moisture generated by heating from 200°C to 900°C (total moisture content).

[0070] [Measurement of the outer edge length L1 of an alumina particle and the total length L2 of the grain boundary inside the particle] Cross-sectional observation specimens were prepared using alumina particles of samples No. 1 to 5. In preparing cross-sectional observation specimens, the alumina particles were embedded in resin, and then the resin and alumina particles were cut with a diamond cutter. Then, Pt was evaporated onto the cross section as a protective film, the cross section was prepared by Ar ion milling, and the specimen was fixed to the SEM specimen stage with Cu double-sided tape, and SEM-EBSD measurement was performed without evaporation. The observation position was determined so that two or more alumina particles were completely within the observation area (i.e., two or more alumina particles did not come into contact with the frame of the observation area). All of the measured alumina particles were α-alumina particles.

[0071] The following equipment was used for sample preparation and EBSD measurement: ·Equipment used Ion milling device: IM-4000 (manufactured by Hitachi, Ltd.) Ion sputtering device: E-1030 (manufactured by Hitachi, Ltd.) Ultra-high resolution field emission scanning electron microscope: JSM-7800F Prime (manufactured by JEOL Ltd.) Backscattered electron diffraction equipment: Digiview V (TSL)

[0072] The EBSD measurement conditions were as follows: ·Measurement area: 500.0μm×400.0μm Acceleration voltage: 20.0 kV Magnification: x500 ·Vacuum degree: 30Pa

[0073] In the obtained EBSD image, two or more alumina particles that were not in contact with the frame of the observation area were selected, and the outer edge length L1 of each alumina particle was averaged using image processing software Image J (National Institute of Health). The "total grain boundary length L2" is the sum of the grain boundaries contained inside the alumina particle, and does not include the outer edge of the alumina particle. The total grain boundary length L2 was calculated by adding the total length of the grain boundaries inside the alumina particle and the total length of the inner wall of the cavity (if there is a cavity inside the alumina particle).

[0074] The ratio of the total grain boundary length L2 to the outer edge length L1 (L2 / L1) is expressed as a percentage (%). The more grain boundaries and cavities there are inside the alumina particle, the higher the value of L2 / L1 (%).

[0075] [Uranium and thorium content of alumina particles] The uranium content (U amount) and thorium content (Th amount) contained in the alumina particles were measured as follows. First, the alumina particles were put into a mixed aqueous solution of sulfuric acid and phosphoric acid, and heated to dissolve the alumina particles, to prepare an aqueous solution. Then, the aqueous solution was contacted with a cyclohexane solution of tributyl phosphate, which is commonly used as an extractant for uranium, to extract the uranium contained in the aqueous solution. Then, the uranium transferred to the aqueous phase by back-extraction by contacting again with pure water was measured by the intensities of U238amu and Th232amu using ICP-MS. A standard solution manufactured by SPEX was used to create a calibration curve.

[0076] [Amount of alpha rays emitted from alumina particles] The amount of alpha radiation emitted from the alumina particles was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of ​​the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas used was PR-10 gas (Ar 90%, CH4 10%).

[0077] [Preparation of resin composition] Alumina particles, resin, etc. were kneaded to prepare resin compositions (samples No. 1 to 5). The types of resins used are shown in Table 1, and the blending amounts of alumina particles are shown in Table 3. Specifically, the resin compositions of Samples No. 1 to 5 were prepared according to the following preparation method. The "resin composition" in Table 5 indicates the resin composition in a cured state.

[0078] (Samples No. 1 to 5) (1) Preparation of varnish A 30% by mass mixed solution was prepared by dissolving the resin shown in Table 1 in the solvent shown in Table 1. Furthermore, a curing agent (4,4-diaminodiphenylmethane (manufactured by TCI)) was added in an amount of 0.074% by mass relative to 100% by mass of the mixed solution to prepare a varnish.

[0079] (2) Preparation of alumina / varnish mixture Alumina particles were added to the obtained varnish and kneaded using a planetary centrifugal mixer (manufactured by Thinky Corporation) to prepare an alumina / varnish mixture.

[0080] (3) Film formation The obtained alumina / varnish mixture was applied onto a PET substrate, and a film was formed using an applicator so that the film thickness after thermal curing would be 150 to 200 μm, thereby obtaining a resin composition before curing.

[0081] (4) Heat curing The obtained resin composition before curing was left to stand at room temperature for 1 hour, then heated at 140°C for 15 minutes, and further vacuum press molded at 140°C for 20 minutes at a pressure of 0.5 MPa using a press molding machine, and then heated at 180°C for 120 minutes at normal pressure to be thermally cured. In this way, cured resin compositions (samples No. 1 to 5) were obtained. In the resin compositions of samples No. 1 to 5, the proportion of solids in the entire resin composition was 95% by volume or more.

[0082] [Table 1]

[0083] Details of the resin types listed in Table 1 are as follows:

[0084] Mesogenic epoxy resin (A) It is a prepolymer obtained by reacting trans-4-{4-(2,3-epoxypropoxy)phenyl}cyclohexyl 4-(2,3-epoxypropoxy)benzoate (an epoxy resin represented by the structural formula below) with 6-hydroxy-2-naphthoic acid.

[0085] [ka]

[0086] Mixture of JP-100 and HP6000 The resin was prepared by mixing JP-100 (manufactured by Nippon Soda Co., Ltd.), an epoxidized polybutadiene, and HP-6000 (manufactured by DIC Co., Ltd.), a naphthalene-based epoxy resin, in a mass ratio of 1:9.

[0087] [Charge amount of resin and resin composition] The charge amount of the resin and the resin composition was measured using a static electricity measuring device under the following conditions. Static electricity measuring instrument: FMX-004 (manufactured by SIMCO) Measurement mode: Low Mode ·Temperature 23℃, humidity 40% A static electricity measuring device was placed at a height of 25 mm from the surface of a 10 cm square test piece to measure the charge potential. The obtained charge potential value is defined as the charge amount.

[0088] [α-ray dose emitted from resin composition] The amount of α-rays emitted from the resin composition was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of ​​the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas used was PR-10 gas (Ar 90%, CH4 10%).

[0089] [Breaking stress of resin composition, absorbed energy until breakage, and correlation coefficient of stress-strain curve until breakage] The breaking stress, absorbed energy until breaking, and correlation coefficient of the stress-strain curve until breaking of the resin composition were measured in accordance with JIS K7161 (2014). Specifically, a tensile test was performed under the following conditions, and the obtained stress-strain curve was analyzed and calculated. Test equipment: Autograph AGS-X (Shimadzu Corporation) Load cell: 1kN - Test piece size: 100mm x 10mm Test environment: 22℃ / 59%RH Analysis software: TRAPEZIUMX

[0090] When the resin composition has a high breaking stress, the strength of the resulting sealing member is improved, and the dimensional stability against external energy such as heat can also be improved. If the resin composition has a high absorbable energy until breakage, the strength of the resulting sealing member is improved, and the dimensional stability against external energy such as heat can also be improved. If the correlation coefficient when the stress-strain curve of the resin composition up to break is linearly approximated is large, it indicates that the resin composition stretches uniformly, which may mean, for example, that the inorganic particles are not agglomerated with each other and are uniformly dispersed in the resin.

[0091] The breaking stress of the resin composition was determined directly from the breaking point of the stress-strain curve. The absorbed energy of the resin composition until it broke was calculated from the area enclosed by the stress-strain curve obtained in the tensile test. The correlation coefficient when the stress-strain curve of the resin composition up to breakage was linearly approximated was determined by analysis using analysis software. The maximum correlation coefficient is 1.0000 (when the stress-strain curve from the start of the test to breakage is a straight line).

[0092] Tables 2 and 3 show various measurement results for the alumina particles, Table 4 shows the type of resin used and the charge amount of the resin, and Table 5 shows various measurement results for the resin composition.

[0093] [Table 2]

[0094] [Table 3]

[0095] [Table 4]

[0096] [Table 5]

[0097] The measurement results are discussed below. The resin compositions of samples Nos. 1 to 4, which satisfied the requirements of the present embodiment, had a charge amount of 0.00 kV. On the other hand, the resin composition of sample No. 5, which did not satisfy the requirements of the present embodiment, had a charge amount of -0.01, and could not be made 0.00 kV.

[0098] In addition, the alumina particles used in the resin compositions of samples No. 1 to 4 are considered to have been well dispersed in the resin because the absolute value of the charge amount is small. As a result, the breaking stress of the resin composition was high. In addition, the absorbed energy until the resin composition broke and the correlation coefficient of the stress-strain curve until the break also showed good results. On the other hand, the alumina particles used in the resin composition of sample No. 5 had a large absolute value of the charge amount, which is believed to have reduced the dispersibility of the alumina particles in the resin and reduced the breaking stress of the resin composition. The absorbed energy until the resin composition broke and the correlation coefficient of the stress-strain curve until the resin composition broke were lower than those of the resin compositions of samples No. 1 to 4.

[0099] Regarding the amount of α-ray radiation, the resin compositions of samples Nos. 1 to 4 had low levels, while the resin composition of sample No. 5 had high levels.

Claims

1. Alumina particles having a moisture content of more than 59.8 ppm when heated from 200° C. to 900° C.; Resin and A resin composition comprising:

2. The resin composition according to claim 1 , wherein the alumina particles generate more than 43.0 ppm of moisture when heated from 200° C. to 550° C.

3. The resin composition according to claim 1 , wherein the alumina particles have an absolute charge value of 0.17 kV or less.

4. Alpha radiation dose is 0.022 cph / cm 2 The resin composition according to claim 1 , wherein the molecular weight is less than 1.

0.

5. The resin composition according to claim 1 , wherein the alumina particles have a ratio (L2 / L1) of a total length L2 of internal grain boundaries to a length L1 of an outer edge of the alumina particles, which ratio is less than 139.1%.

6. The resin composition according to any one of claims 1 to 5 is used. A sheet molding compound having a thickness of 1000 μm or less.

7. Alumina particles which generate moisture of more than 59.8 ppm when heated from 200°C to 900°C.

Citation Information

Patent Citations

  • Resin composition, cured product, sealing film, and sealing structure

    JP2020200478A